EFFICACY OF TRICHOGRAMMA CHILONIS ISHII IN COMPARISON WITH TWO COMMONLY USED INSECTICIDES AGAINST SUGARCANE STEM BORER CHILO INFUSCATELLUS SNELLEN (L EPIDOPTERA: PYRALIDAE) - F. Ullah; M. Shakur; H. Badshah; S. Ahmad M. Amin; M. Zamin (Journal of Animal and Plant Sciences, 2012)
Relative effectiveness of egg parasitoid Trichogramme chilonis and the two commonly used insecticides, Basudin 60 EC and Furadan 3G against sugarcane stem borer Chilo infuscatellus was evaluated in sugarcane fields under RCB design. Results revealed that highest mean percent parasitism was observed in (Trichocard released plot (T3) 50.46 followed by check plot) (T4) 12.54 while in Basudin treated plot (T1) mean percent parasitism was 8.70 and in Furadan treated plot (T2) the mean percent parasitism was 7.91. All these treatments were found effective for the management of sugarcane stem borer. However the cost and benefit analysis shows that maximum return (84.788) was obtained from Trichocards released plots so, trichocards are recommended for the management of sugarcane stem borer instead of insecticides. Moreover, this practice may have significant role to protect the soil and conserve the natural resources from insecticides contamination.
Keywords: Trichogramma chilonis Ishii; insecticide; Chilo infuscatellus; Control